Doppler study of umbilical and fetal middle cerebral artery in severe preeclampsia and intra uterine growth restriction and correlation with perinatal outcome - Singh, Santosh Kumar; Mishra, Priti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pre-eclampsia and IUGR are two conditions resulting from defective trophoblastic invasion of spiral arteries and an increase in vascular resistance in uteroplacental circulation. Doppler offers a non-invasive tool for evaluation of fetoplacental blood flow and correlate with fetal compromise giving early warning sign of fetal distress. Methods: The study was conducted in Command Hospital, Lucknow in 100 singleton pregnancies with vertex presentation between 28-40 weeks of gestation with severe preeclampsia and/or IUGR. Doppler analysis of UA and MCA was done. Pregnancies were terminated depending on clinical condition and Doppler results. Results: Abnormal Umbilical artery S/D ratio had strong statistical correlation with poor perinatal outcome. Elevated RI had 100% sensitivity in predicting APGAR<7 at 5 minutes. Elevated PI values was statistically significant in all parameters (except NICU stay>48hrs) in predicting poor perinatal outcome. PI values had highest sensitivity for predicting low APGAR values and highest specificity for predicting NICU admission. AEDF and REDF also correlated with adverse perinatal outcome. MCA S/D ratio had a high sensitivity (96.8%) in determining NICU stay>48h and specificity (70%) in determining NICU admissions. RI had highest sensitivity (71.8%) for NICU stay >48hrs and highest specificity for predicting NICU admissions (76.5%). MCA PI had a sensitivity of 66.6% in determining APGAR<7 at 5min and a specificity of 78.7% in determining NICU admissions. CPR had the highest sensitivity (100%) among all indices. Conclusions: The study showed an adverse fetal outcome in cases of severe preeclampsia and or IUGR which showed abnormal Doppler results and thereby help to determine the optimal time for delivery.